The influence of the health level of sharia bank using the RGEC method on third party funding and profitability: Study at Bank Syariah Mandiri Period 2013-2020 - Marwati; Sakum; Hamdan Ainul Yaqien (NUsantara Islamic Economic Journal, 2023)
The health of a financial institution is in the interest of all related parties, both capital owners and bank managers, people who use bank services, and OJK as the owner of the authority in supervising banks. A healthy bank is a bank that can carry out its functions well, namely being able to maintain and maintain public trust, can carry out the intermediation function, can assist payment traffic and can be used by the government in carrying out various monetary policies, and most importantly can improve performance. financial form of profit or profitability. This study aims to analyze the effect of Islamic bank health level using the RGEC (Risk Profile, Good Corporate Governance, Earning, and Capital) method on third party fund raising and profitability. This study uses a descriptive quantitative research method, with the independent variable being the Soundness of Islamic Banks Using the RGEC Method with indicators of CAR, NPF, FDR, NOM, BOPO. As for the dependent variable, namely Third Party Funds and Profitability (ROA). Data collection techniques used secondary sources with data analysis using multiple linear regression analysis with the help of IBM SPSS 20. The results showed that the Health Level of Bank Syariah Mandiri in 2013-2020 experienced an increase in the CAR ratio which was categorized as very good. Likewise, the ratio of NPF and FDR is in the Good category. However, the NOM ratio is categorized as Bad. While the BOPO ratio is categorized as Very Good. Likewise, the ROA ratio is categorized as Good Enough. Meanwhile, the collection of third party funds increased by 2.59% or equivalent to 2.018 billion per quarter. Together (simultaneously) the variables of bank soundness, namely CAR, NPF, FDR, NOM, and BOPO have a significant influence and are able to explain the Third Party Fund (DPK) variable of 37.3%. Likewise, the Profitability (ROA) variable has a significant influence and is able to explain 99.9%. While individually (partial) CAR, NPF, FDR, BOPO have no significant effect on Third Party Funds and Profitability (ROA). However, NOM has a significant effect on Third Party Funds and Profitability (ROA).